2007
DOI: 10.1080/02786820601055392
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Emissions from a Low-Speed Marine Diesel Engine

Abstract: This study presents results from tail pipe emissions of particulate matter from a turbocharged common rail 2-stroke marine diesel engine (4RTX-3 from Wärtsilä) investigated at various operating conditions and using two different fuels. Size distributions were measured with a SMPS (Scanning Mobility Particle Sizer). A thermodesorber (TD) was applied to remove volatile material. In addition, filter samples were taken for gravimetric and chemical analysis. The mean diameters of the particles ranged between 20-40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
124
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(144 citation statements)
references
References 12 publications
(14 reference statements)
11
124
2
2
Order By: Relevance
“…A corresponding figure for MDO with 0.155% sulfur is in the same range but with a much lower total mass. 15 The chemical composition and sulfur content of the particles have also been reported to vary with engine load during HFO combustion. 14,24 The importance of sulfur content on mass emissions of particles is well known.…”
Section: Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…A corresponding figure for MDO with 0.155% sulfur is in the same range but with a much lower total mass. 15 The chemical composition and sulfur content of the particles have also been reported to vary with engine load during HFO combustion. 14,24 The importance of sulfur content on mass emissions of particles is well known.…”
Section: Loadmentioning
confidence: 99%
“…Test bed studies by engine manufacturers are seldom published and in many cases concern new engines. Published research results from test bed emission studies include Lyyränen's work, [12][13][14] which considered engines for marine application and with residual oil only, and Kasper et al, 15 who examined particle formation from combustion of heavy fuel oil (HFO) as well as a MDO.…”
Section: Introductionmentioning
confidence: 99%
“…Sulphate particles in the exhaust system form during the cooling of the exhausts and a reaction between SO 3 and water, which forms H 2 SO 4 . Kasper et al (2007) found that 1.4% of the sulphur in the fuel was in the form of sulphate in exhaust gas particles. Agrawal et al (2008) showed a sulphate particle formation between 7% and 5% for the same mechanisms during exhaust gas measurements after dilution with air, while Moldanová et al (2009) concluded on 1.3%.…”
Section: Introductionmentioning
confidence: 99%
“…Sulphur is chemically bonded to the hydrocarbons of the fuel and during combustion; most suphur is oxidized to SO 2 (MAN B&W Diesel, 1996). Sulphur, which is mostly oxidized to SO 2 during combustion, is a major constituent of the primary particles in the exhaust from gasoline and diesel powered engines from the combustion of fuel (Kasper et al, 2007;Agrawal et al, 2008;Petzold et al, 2008;Moldanová et al, 2009;Popovicheva et al, 2009). Sulphate particles in the exhaust system form during the cooling of the exhausts and a reaction between SO 3 and water, which forms H 2 SO 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation